Positioned as pedagogues, finding their teaching personas: critical, project-based clinical experiences in PDS/school-university contexts - Kristien Zenkov; Marion Taousakis; Jennifer Goransson; Emily Staudt; Marriam Ewaida; Madelyn Stephens; Megan Hostutler; Jasmin Castorena; Matt Kitchen (School-University Partnerships)
Purpose – Policy makers, professional associations and scholars continue to advocate for the integration of enhanced clinical experiences for future teachers’ preparation. These recommendations reflect the growing recognition that few events in preservice teachers’ education are more significant than their experiences in the classrooms of veteran peers. Aware of the fact that the field of teacher education needs examples of effective clinical experiences, the authors examined the “critical, project-based” (CPB) model, employing Photovoice activities in a dropout prevention course in a secondary education partner school at the beginning of the COVID-19 pandemic. This paper aims to discuss the aforementioned objective. Design/methodology/approach – Aware that the field of teacher education needs examples of effective clinical experiences, the authors examined the CPB model, employing Photovoice activities in a dropout prevention course in a secondary education partner school at the beginning of the COVID-19 pandemic. In this article they detail a practitioner research examination that explores the experiences of 12 preservice middle/high school teachers, reporting on these individuals’ considerations of general pedagogies, writing instruction strategies and teaching personas. Findings – Results suggest that preservice teachers might best identify pedagogical practices that are consistent with their nascent teaching identities via experiences that occur in school-university partnerships in which future teachers are positioned as pedagogues. Originality/value – This manuscript explores the use of the “CPB” clinical experience model, identifying the impacts of this approach for preparing future teachers.